2014
DOI: 10.1111/tmi.12331
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Assessing the impact of drinking water and sanitation on diarrhoeal disease in low‐ and middle‐income settings: systematic review and meta‐regression

Abstract: Abstractobjective To assess the impact of inadequate water and sanitation on diarrhoeal disease in lowand middle-income settings.methods The search strategy used Cochrane Library, MEDLINE & PubMed, Global Health, Embase and BIOSIS supplemented by screening of reference lists from previously published systematic reviews, to identify studies reporting on interventions examining the effect of drinking water and sanitation improvements in low-and middle-income settings published between 1970 and May 2013. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
378
3
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 407 publications
(395 citation statements)
references
References 68 publications
10
378
3
4
Order By: Relevance
“…Continuous supply, water quality, and storage emerged as mediating factors for health benefits of piped on-plot water, consistent with recent review findings (Wolf et al, 2014). A recent multi-country study found differences in water quality by water source type (Evans et al, 2013), but included studies reported little data on water quality by source type.…”
Section: Discussionsupporting
confidence: 77%
“…Continuous supply, water quality, and storage emerged as mediating factors for health benefits of piped on-plot water, consistent with recent review findings (Wolf et al, 2014). A recent multi-country study found differences in water quality by water source type (Evans et al, 2013), but included studies reported little data on water quality by source type.…”
Section: Discussionsupporting
confidence: 77%
“…The majority (84 %) reported no incidents of digestive afflictions, including diarrhoea, in the family during the last 5 years. This was supported by an official statement by the Hobeni Clinic, although morbidity rates depend on self-reporting from the household members, which is known to produce substantial bias (Wolf et al, 2014;Clasen et al, 2015). Also, the microbiological water quality of 51 tested CCFSs showed contrasting results: none of the filtrate samples was free of coliform bacteria and 35 % even showed a deterioration in water quality (Fig.…”
Section: Field Surveymentioning
confidence: 81%
“…BSF with plastic housing was found to be as efficient as its concrete counterparts (Fabiszewski de Aceituno et al, 2012) and various researchers reported the success of locally produced, low-cost CWF Simonis and Basson, 2011;Mwabi et al, 2013). Recent reviews of reduction of diarrhoea by different POU interventions found filtration techniques superior to solar or chemical water disinfection (Wolf et al, 2014;Clasen et al, 2015). However, comparisons were blurred by a high risk of bias, since the data relied on self-reported diarrhoea and placebo POU interventions were missing.…”
Section: Introductionmentioning
confidence: 99%
“…Rural areas of Sub-Saharan Africa suffer from limited access to improved water sources and high risk of fecal contamination in drinking water. Household water treatment and safe storage (HWTS) has been proposed as an intermediate solution to provide safer drinking water and reduce the burden of disease (WHO/UNICEF, 2008;Wolf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%